An Evaluation Of The Government's Involvement In The Fct Abuja, Nigeria, Poverty Eradication Program. - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Regardless of ethnicity, gender, or social standing, poverty and injustice are twain plaques that are ruining lives and undermining the core of existence, according to the examiner. As a result of the unimaginable devastation, world leaders and As societal systems are being exhausted, policymakers are searching for solutions; mobility rates have increased, and the discourse surrounding income distribution is tainted. While other nations who are severely overburdened are struggling to understand the realities of these economic thunderbolts, others that have recognized these terrible patterns are formulating plans to counter the escalating threat. The purpose of the study is to look into the causes and antecedent effects of poverty on the Nigerian economy because, in spite of the admirable efforts made by the federal, state, and local governments to reduce and eradicate poverty, the nation is still plagued by widespread poverty and issues with property and life insecurity, endangering the nation's ability to remain an indivisible whole. Although there are more than a billion people in Africa, Nearly half of the population is impoverished and at risk, and this number is still rising (World Population Review, 2014). With a population of more than 170 million, Nigeria is battling not only poverty but also a host of other problems, such as a lack of capable leaders, corruption, deteriorating infrastructure, and problems with nutrition and health. In order to gather data, the study used a descriptive technique with questionnaires; 80 questionnaires were recovered and 120 were randomly dispersed to the respondents. According to the findings, poverty has increased, which has resulted in incidents like armed robberies, prostitution, bombings, and insecurity of life and property. The document makes several recommendations, including that the government develop workable programs and give young people the tools they need to become self-sufficient.